Early Childhood Board Games with School Objects and Anatomical Theme to Facilitate Learning - Putra, Anak Agung Adi Wiryya; Surjono, Herman Dwi (Universitas Pendidikan Ganesha, 2023)
Early childhood's low understanding of basic material such as school objects and anatomy will have an adverse impact on the next level of education. The purpose of this research is to produce and find out the effectiveness of board games learning media that can facilitate the early childhood learning process on the topic of school objects and anatomy. This research type is research and development with the APPED model. The subjects in the study consisted of early childhood students, 3 teachers, and 3 validators. Collecting data are using interviews, observation, and questionnaires. The instruments used were interview guides, questionnaires for material experts and media experts, pretest, post test, and data analysis using descriptive analysis techniques. The results of the research resulted in a board game product with a material feasibility test result of 4.7 and a media feasibility test of 4.1. The effectiveness test with pretest and post test activities showed that there was an increase in children's understanding from a score of 50.6 to 82.6. Board games with the topic of school objects and anatomy are appropriate and effective for use in early childhood learning.